2020
DOI: 10.1021/acssynbio.0c00514
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Biogenesis of a De Novo Designed Iron–Sulfur Protein

Abstract: In vivo expression of metalloproteins requires specific metal trafficking and incorporation machinery inside the cell. Synthetic designed metalloproteins are typically purified without the target metal, which is subsequently introduced through in vitro reconstitution. The extra step complicates protein optimization by high-throughput library screening or laboratory evolution. We demonstrate that a designed coiled-coil iron−sulfur protein (CCIS) assembles robustly with [4Fe-4S] clusters in vivo. While in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The few reported examples of in vivo metal incorporation rely on structural motifs that permit covalent attachment of a cofactor such as c -type hemes or bilins. , Control of in vivo metal or cluster incorporation without covalent attachment remains unsolved. A recent study used the previously reported CCIS scaffold to investigate the differences between in vivo and in vitro [4Fe-4S] metalation of this construct . CCIS had been previously reconstituted in vitro using FeCl 3 , Na 2 S, and DTT under anaerobic conditions, but it showed batch to batch variability with different mixtures of oligomers …”
Section: Non-heme Electron Transfer Sitesmentioning
confidence: 99%
See 3 more Smart Citations
“…The few reported examples of in vivo metal incorporation rely on structural motifs that permit covalent attachment of a cofactor such as c -type hemes or bilins. , Control of in vivo metal or cluster incorporation without covalent attachment remains unsolved. A recent study used the previously reported CCIS scaffold to investigate the differences between in vivo and in vitro [4Fe-4S] metalation of this construct . CCIS had been previously reconstituted in vitro using FeCl 3 , Na 2 S, and DTT under anaerobic conditions, but it showed batch to batch variability with different mixtures of oligomers …”
Section: Non-heme Electron Transfer Sitesmentioning
confidence: 99%
“…Process of producing [4Fe-4S] cluster bound CCIS in vitro vs in vivo . Reprinted with permission from ref . Copyright 2020 American Chemical Society.…”
Section: Non-heme Electron Transfer Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Because metal uptake and delivery is carefully controlled by all organisms, particularly for late transition metals, incorporation of non-native metals into overexpressed proteins has remained a challenge in the field. Recent advances have demonstrated in vivo incorporation of [4Fe-4S] clusters into de novo designed peptides and assembly of c -type hemes into engineered protein scaffolds. , These approaches harness the innate biochemical machinery present in E. coli for c -type cytochrome and iron–sulfur ([FeS]) cluster maturation. As an alternative method, insertion of a complete, fully synthetic cofactor has also been shown to result in proper in vivo assembly of [FeFe] hydrogenases, which has application to generating such enzymes from an array of organisms and within diverse hosts .…”
mentioning
confidence: 99%